Information Externalities in the Labour Market and the Duration of Unemployment - Lockwood, Ben (Review of Economic Studies, 1991)
A matching model is analyzed in which firms imperfectly test workers prior to hiring them. If (some) firms hire only workers who pass the test, there is an informational externality; unemployment duration is a signal of productivity. In equilibrium, if it is profitable for a firm to test, it is also profitable for it to condition its hiring decision on duration, hiring those whose duration is less a than critical value. Sensitivity analysis of the latter suggests explanations for the dependence of reemployment probabilities on duration and the instability of the U-V curve. Copyright 1991 by The Review of Economic Studies Limited.